2013
DOI: 10.1371/journal.pone.0077203
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Intestinal Epithelial Apoptosis Improves Survival in a Murine Model of Radiation Combined Injury

Abstract: World conditions place large populations at risk from ionizing radiation (IR) from detonation of dirty bombs or nuclear devices. In a subgroup of patients, ionizing radiation exposure would be followed by a secondary infection. The effects of radiation combined injury are potentially more lethal than either insult in isolation. The purpose of this study was to determine mechanisms of mortality and possible therapeutic targets in radiation combined injury. Mice were exposed to IR with 2.5 Gray (Gy) followed fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 41 publications
2
6
0
Order By: Relevance
“…CSF 3 receptor is the primary high-affinity receptor for G-CSF and uses the Janus kinase/signal transducer and activator of transcription and V-Yes-1 Yamaguchi Sarcoma Viral Related Oncogene Homolog signal transduction pathways. 36 , 37 , 38 , 39 Furthermore, SOCS3, BCL2A1, and CXCR2 are induced in response to G-CSF activity. G-CSF pathway activation includes dendritic cell differentiation, neutrophil mobilization, and, more generally, cell survival.…”
Section: Discussionmentioning
confidence: 99%
“…CSF 3 receptor is the primary high-affinity receptor for G-CSF and uses the Janus kinase/signal transducer and activator of transcription and V-Yes-1 Yamaguchi Sarcoma Viral Related Oncogene Homolog signal transduction pathways. 36 , 37 , 38 , 39 Furthermore, SOCS3, BCL2A1, and CXCR2 are induced in response to G-CSF activity. G-CSF pathway activation includes dendritic cell differentiation, neutrophil mobilization, and, more generally, cell survival.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, there are no readily available pharmacological agents that offer effective mitigation of RIGS, and as such there is great interest in developing such mitigators. 1 - 3 For clinical radiation therapy of thoracic, abdominal, and genitourinary cancers, the collateral irradiation of abdominal tissue is often dose limiting.…”
Section: Introductionmentioning
confidence: 99%
“…4 Much of the current knowledge about RIGS comes from small animal models mainly utilizing mice. [1][2][3]5,6 As the Food and Drug Administration requires the effect of radiation mitigators to be proven in separate animal models, studies have also been conducted using nonhuman primates and minipigs. [7][8][9] Death from HS occurs at lower radiation doses compared to RIGS, so partial bone marrow shielding is needed to investigate the long-term (>20 days) efficacy of mitigators for acute abdominal toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…20 Immune cell populations respond differently depending upon which compartment they are in. 21 In studies combining radiotherapy and immunotherapy, NK cells sensitize the tumor cells to radiation and the radiation sensitizes the tumor cells to NK cell attack. 22 It was also observed that CD244.2 mediates NK/NKT-like cell activation with its mediated signaling contributing both positively and negatively to viral clearance and immune mediated diseases.…”
Section: Discussionmentioning
confidence: 99%